2015
DOI: 10.1007/s12031-014-0485-2
|View full text |Cite
|
Sign up to set email alerts
|

S100 Alone Has the Same Destructive Effect on Retinal Ganglion Cells as in Combination with HSP 27 in an Autoimmune Glaucoma Model

Abstract: As previously shown, immunization with ocular antigens, like heat shock protein 27 (HSP 27), leads to retinal ganglion cell loss in an autoimmune glaucoma model. Aim of this study was to assess how immunization with S100 alone and in combination with HSP 27 affects retinal ganglion and macroglia cells. Rats were immunized with S100 or S100 plus HSP 27 (COMB). Neuronal cell density was evaluated on Nissl-stained flatmounts. Immunized groups showed a significant neuronal cell loss (S100, p = 0.005; COMB, p = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…Although only few changes in the mRNA expression of GFAP were noted in this study after 14 days. Previous results of our group revealed a reactive gliosis at later points in time [4]. Here, phosphacan expression in Müller glia occurs earlier following retinal and optic nerve damage than gliosis in this model.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Although only few changes in the mRNA expression of GFAP were noted in this study after 14 days. Previous results of our group revealed a reactive gliosis at later points in time [4]. Here, phosphacan expression in Müller glia occurs earlier following retinal and optic nerve damage than gliosis in this model.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, we analyzed the expression pattern of the ECM glycoprotein tenascin-C and the CSPG phosphacan/RPTPb/f in an IOPindependent EAG model. Data from previous studies showed a loss of RGCs in the ONA as well as in the S100 group 28 days after immunization [4,5]. Here, we investigated possible ECM alterations in this model at earlier points in time.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In previous studies, immunization with HSP27, a purified antigen, led to loss of RGCs. 15,16 In addition to autoantibodies to HSP27, elevated antibodies against the glial cell line-derived neurotrophic factor (GDNF) were found in glaucoma patients with normal tension. It is still unclear if the antibodies found in glaucoma patients are the cause or the consequence of the disease.…”
mentioning
confidence: 99%
“…Um den Zusammenhang zwischen einer Dysregulation des Immunsystems und dem Glaukom besser untersuchen zu können, wurde das Experimentelle Autoimmune Glaukommodell (EAG-Modell) entwickelt. In diesem Modell kommt es, unabhängig vom IOD, nach 28 Tagen zu einem Verlust von RGZ und einer Degeneration der Sehnerven [21,22]. Durch die Immunisierung mit okulären Antigenen, wie z.…”
Section: Therapeutische Modulation Des Komplementsystemsunclassified